(untitled) (KIUT Publication, 2025)
A new method based on electric motor control has been proposed to optimize the operating modes of units at pump stations. Using this method, calculations demonstrate that by adjusting the motor speed by 10 revolutions per minute, the pump’s water discharge capacity can be changed by 3–4 m³/s.